2020
DOI: 10.3892/etm.2020.8652
|View full text |Cite
|
Sign up to set email alerts
|

Significance of changes in inflammatory parameters following uterine artery embolization in pre‑menopausal females

Abstract: The purpose of the present study was to describe the course of changes in laboratory inflammatory markers following bilateral uterine artery embolization (UAE) as a treatment for leiomyomas and adenomyosis. The body temperature was measured and blood samples were collected to determine white blood cell (WBC) count and C-reactive protein (CRP) levels in 270 patients on the day prior to UAE and for up to 4 days post-embolization. Aside from a single case with a non-inflammatory complication, none of the other ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…PES is caused by avascular necrosis of the muscle layer after UAE, which induces the release of cytokines and causes systemic inflammation ( 21 ). Previous studies have shown that glucocorticoids can reduce pain, nausea, and vomiting ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…PES is caused by avascular necrosis of the muscle layer after UAE, which induces the release of cytokines and causes systemic inflammation ( 21 ). Previous studies have shown that glucocorticoids can reduce pain, nausea, and vomiting ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively old data reveal that serum CRP titers can be more than 3 mg/L in women with endometriosis and uterine fibroids, and other data indicate that it is a marker of clinical importance in determining possible reproductive failure, whereas a more recent study showed that following bilateral Uterine Artery Embolization (UAE) as a treatment for leiomyomas and adenomyosis, CRP concentrations can be increased (a median of approx. 80 mg/L) [ 395 , 396 , 397 ]. In addition, other data show CRP levels above the cutoff level of 0.71 mg/L were independently linked to former Cervical Artery Dissection (CAD) regardless of conventional risk factors [ 398 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%
“…In Table 1 are summarized the complications in our participants and according to international literature with the maximally respectively referred complications rate. The first column of the table refers to our results in the time from 2008 to 2020 while in the second column are shown the respective values of the examinated parameters in average concerning to international literature [72][73][74][75][76].…”
Section: Postprocedureal Managementmentioning
confidence: 99%